Effective Two-Stage Heterotrophic Cultivation of the Unicellular Green Microalga Chromochloris zofingiensis Enabled Ultrahigh Biomass and Astaxanthin Production - Chen, Qiaohong; Chen, Yi; Xu, Quan; Jin, Hu; Hu, Qiang; Han, Danxiang (Frontiers in Bioengineering and Biotechnology, 2022)
Chromochloris zofingiensis has obtained particular interest as a promising candidate for natural astaxanthin production. In this study, we established a two-stage heterotrophic cultivation process, by using which both the growth of C. zofingiensis and astaxanthin accumulation are substantially enhanced. Specifically, the ultrahigh biomass concentration of 221.3 g L−1 was achieved under the optimum culture conditions in 7.5 L fermenter during 12 days. When scaled-up in the 500 L fermentor, the biomass yield reached 182.3 g L−1 in 9 days, while the astaxanthin content was 0.068% of DW. To further promote astaxanthin accumulation, gibberellic Acid-3 (GA3) was screened from a variety of phytohormones and was combined with increased C/N ratio and NaCl concentration for induction. When C. zofingiensis was grown with the two-stage cultivation strategy, the astaxanthin yield reached 0.318 g L−1, of which the biomass yield was 235.4 g L−1 and astaxanthin content was 0.144% of DW. The content of the total fatty acids increased from 23 to 42% of DW simultaneously. Such an astaxanthin yield was 5.4-fold higher than the reported highest record and surpassed the level of Haematococcus pluvialis. This study demonstrated that heterotrophic cultivation of C. zofingiensis is competitive for industrial astaxanthin production.